2012
DOI: 10.2166/wst.2012.880
|View full text |Cite
|
Sign up to set email alerts
|

MBR technology: a promising approach for the (pre-)treatment of hospital wastewater

Abstract: Membrane bioreactor (MBR) technology is a very reliable and extensively tested solution for biological wastewater treatment. Nowadays, separate treatment of highly polluted wastewater streams especially from hospitals and other health care facilities is currently under investigation worldwide. In this context, the MBR technology will play a decisive role because an effluent widely cleaned up from solids and nutrients is absolutely mandatory for a subsequent further elimination of organic trace pollutants. Taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The pre-treatment activities were carried out in a membrane bioreactor (JVIBR) pilot plant followed by laboratory tesfing of four polishing technologies: ozone (O3), ozone-I-hydrogen peroxide (O3-fH2O2), powdered activated carbon (PAC) and chlorine dioxide (CIO2). MBR technology was chosen because of a lower footprint and more efficient removal of micropollutants than convenfional treatment plants and because it provides a significant hygienizafion of sewage water (Ottoson et al 2006;Radjenovic et al 2009;Beier et al 2012), The chosen polishing technologies are from a mechanisfic point of view pofenfially effective on micropollutants such as APIs.…”
Section: Introductionmentioning
confidence: 99%
“…The pre-treatment activities were carried out in a membrane bioreactor (JVIBR) pilot plant followed by laboratory tesfing of four polishing technologies: ozone (O3), ozone-I-hydrogen peroxide (O3-fH2O2), powdered activated carbon (PAC) and chlorine dioxide (CIO2). MBR technology was chosen because of a lower footprint and more efficient removal of micropollutants than convenfional treatment plants and because it provides a significant hygienizafion of sewage water (Ottoson et al 2006;Radjenovic et al 2009;Beier et al 2012), The chosen polishing technologies are from a mechanisfic point of view pofenfially effective on micropollutants such as APIs.…”
Section: Introductionmentioning
confidence: 99%
“…Berto et al (2009) reported a total coliform concentration of 2 × 10 8 MPN/100 ml and a thermotolerant coliform concentration of 1.6 × 10 8 MPN/100 mL in Brazil [43] . Beier et al (2012) reported E. coli, fecal coliform, and enterococci in the range of 10 3 to 10 6 MPN/100 mL [57] . In a hospital effluent of France, the E. coli concentration varied from 8.3×10 4 CFU/mL 3×10 5 CFU/mL [58] , [59] .…”
Section: Characteristics Of Hospital Wastewatermentioning
confidence: 99%
“… 165.75 L/day 4 days Pilot-scale [12] , [97] Study 13 Finland Ultrafiltration followed by pulsed corona discharge (30 W was applied for 1 kWh /m 3 of pulse energy delivered) Pilot-scale [119] Study 14 Spain MBR (11 m 3 ) with 10 flat sheet (FS) chloral polyethylene membranes (0.8 m 2 each). Coarse bubble aeration was provided, MLSS- 8 g/L 100 L/h 50 h 30 days [100] Study 15 France Activated sludge incorporated with biofilms followed by ultrafiltration, Dissolved oxygen: 1 to 4.5 mg/L 100 L/day 22 h 20 days [90] Study 16 Germany The unit comprised of a MBR: Membrane area per module = 320 m 2 , Total membrane area = 1,600 m 2 130 m 3 /day 31.3 h Pilot-scale [57] Study 17 Germany MBR comprising of Mesh, primary settling tank (21 m 3 : HRT= 1 h), Oxic/anaerobic chamber (56 m 3 , suspended solid concentration= 10 to 12 g/L), microfiltration (102 m 3 ) followed by NF/RO 130 m 3 /day Pilot-scale [104] Study 18 Greece Pre-treatment (grit-removal), a mix tank, and a biological secondary treatment- Aeration tank (600 m 3 ) followed by disinfection (chlorine dose 10 to 20 mg/L) 6 h 11 days …”
Section: Pilot/full-scale Treatment Systems For Hww Managementmentioning
confidence: 99%
“…Most of the investigations referred to pilot/lab scale plants (69%) and the remaining 31% to full scale dedicated facilities (see Table SD-1 in the Supplementary data). The latter include the following treatment trains: septic tank followed by an anaerobic filter (Brazil, de Almeida et al, 2013;Martins et al, 2008); UASB + anaerobic filters (Brazil, Prado et al, 2011); series of maturation and facultative ponds (Ethiopia, Beyene and Redaie, 2011); septic tank + constructed wetlands (H-SSF + V-SSF beds) (Nepal, Shrestha et al, 2001); MBR (in Germany, Beier et al, 2011Beier et al, , 2012in China: Liu et al, 2010;Wen et al, 2004); CAS + chlorination (in Greece, Kosma et al, 2010;in Brazil, Prado et al, 2011;in Iran, Mahvi et al, 2009) Moreover, 53% of the studies were carried out in European countries (Austria, Belgium, Denmark, France, Germany, Greece, Italy, Luxembourg, Netherlands, Switzerland and Turkey), 27% in Asiatic countries (China, India, Indonesia, Iran, Iraq, Nepal, Republic of Korea, Thailand and Taiwan), 16% in South America (Brazil) and 4% in Africa (Egypt and Ethiopia). PhCs were detected and removal efficiencies were evaluated in 60% of the studies included, whereas the remaining ones only refer to conventional parameters.…”
Section: Technologies and Treatment Trains For Hww Under Reviewmentioning
confidence: 99%